СEREAL LURE FOR IMPROVEMENT OF INTESTINAL MICRO FLORA COMPOSITION IN CHILDREN IN INFANCY - T.E. Borovik; V.A. Skvortsova; S.G. Makarova; O.K. Netrebenko; O.L. Lukoyanova; Yu.S. Akoev; N.N. Semenova; T.N. Stepanova (Вопросы современной педиатрии, 2009)
Authors analyzed a data on composition of modern industrially produced paps. The terms «pro and prebiotical products» was defined. It was shown, that these products influenced on composition of intestinal micro flora, functional state of gastrointestinal tract, and opportunity of prophylaxis of alimentary allergy in children in first year of life. This article describes good tolerance and significant effectiveness of milk free pap «Pomogayka» containing oats, wheat and prunes, enriched with sinbiotics: oligofructose, inulin, and bifidobacterium.Key words: children in infancy, probiotics, prebiotics, alimentary allergy, intestinal disbiosis.(Voprosy sovremennoi pediatrii — Current Pediatrics. 2009;8(3):99-103)